Solvability of nonlinear elliptic systems with measure - Kalita, E. A. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We prove the solvability of nonlinear elliptic systems in spaces dual to the Morrey spaces. As a main consequence, we establish that, under certain restrictions on the modulus of ellipticity of a system, systems with measure are solvable.